Associations among Motor Competence, Physical Activity, Perceived Motor Competence, and Aerobic Fitness in 10-15-Year-Old Youth - Dawn P. Coe; Emily M. Post; Eugene C. Fitzhugh; Jeffrey T. Fairbrother; E. Kipling Webster (MDPI AG, 2024)
(1) Background: The developmental model describes possible mechanisms that could impact the trajectory of children and adolescents' health behaviors related to obesity; however, few data are available that support this model in the adolescent population. This study investigated the associations among motor competence (MC), moderate-to-vigorous physical activity (MVPA), perceived motor competence (PMC), and aerobic fitness in children and adolescents and the mediating and moderating effects of PMC, aerobic fitness, and weight status on the MC-MVPA relationship. (2) Methods: Participants included 47 adolescents (12.2 ± 1.6 y; 55% male) who completed the Bruininks-Oseretsky Test of Motor Proficiency, 2nd Edition (MC), Harter's perceived self-competency questionnaire (PMC), and the PACER test (aerobic fitness) and whose MVPA was measured via accelerometry. The body mass index (BMI) was calculated from measured height and weight. (3) Results: There were positive correlations between MC and fitness [rs(47) = 0.469, p < 0.01], PMC and fitness [rs(47) = 0.682, p < 0.01], and PMC and MC [rs(47) = 0.416, p < 0.01]. There were no associations among MVPA and MC, PMC, or fitness (p > 0.05). There were inverse associations between BMI and both MVPA [rs(44) = −0.410, p < 0.01] and fitness [rs(47) = 0.295, p < 0.05]. The association between MC and MVPA was mediated by fitness (β = 0.3984; 95% CI (0.0564-0.7985)). (4) Conclusions: The associations among MC, PMC, and fitness highlight the critical role of MC in health and partially support the proposed developmental model concerning the relationships that exist among MC, MVPA, PMC, fitness, and BMI.